Association of leisure-time physical activity and resistance training with risk of incident hypertension: The Ansan and Ansung study of the Korean Genome and Epidemiology Study (KoGES) - Park, Jae Ho; Lim, Nam-Kyoo; Park, Hyun-Young (Frontiers in Cardiovascular Medicine, 2023)
Hypertension is the most common preventable risk factor for the onset of cardiovascular disease and mortality. We aimed to investigate the association between incident hypertension and 4-year leisure-time physical activity (PA) levels and resistance training (RT). In this community-based Korean cohort, 5,075 participants without hypertension were included. To evaluate cumulative PA, the average PA time (the total time of moderate-intensity leisure-time PA) at baseline, 2-year follow-up, and 4-year follow-up were calculated. Based on participation in RT and compliance to PA guidelines (≥150 min/week of PA time), the participants were divided into the following four groups: Low-PA, Low-PA+RT, High-PA, and High-PA+RT. A multivariate Cox proportional hazards regression model was used to evaluate the 12-year incidence of hypertension in relation to leisure-time PA levels and RT regularity. During a mean 7.86 ± 4.20-year follow-up, 2,544 participants (1,366 women) were diagnosed with hypertension. Compared with Low-PA, High-PA, and High-PA+RT decreased the risk for hypertension by 30 and 39%, respectively. Participation in RT without compliance to PA guidelines did not affect the incidence of hypertension. The additive effect of RT on hypertension in the High-PA group was further examined. Although sex-based comparisons indicated that men had a significantly longer training period for RT than women, an additional reduction in the risk for hypertension in relation to the addition of RT was observed only in women (35%). PA may confer protective effects against hypertension, whereas the addition of RT to high levels of PA can further reduce the risk for hypertension in women.